Reduced crown root number improves water acquisition under water deficit stress in maize (Zea mays L.) - Gao, Yingzhi; Lynch, Jonathan P. (Journal of experimental botany, 2016)
In this study we test the hypothesis that maize genotypes with reduced crown root number (CN) will have greater root depth and improved water acquisition from drying soil. Maize recombinant inbred lines with contrasting CN were evaluated under water stress in greenhouse mesocosms and field rainout shelters. CN varied from 25 to 62 among genotypes. Under water stress in the mesocosms, genotypes with low CN had 31% fewer crown roots, 30% deeper rooting, 56% greater stomatal conductance, 45% greater leaf CO₂ assimilation, 61% net canopy CO₂ assimilation, and 55% greater shoot biomass than genotypes with high CN at 35 days after planting. Under water stress in the field, genotypes with low CN had 21% fewer crown roots, 41% deeper rooting, 48% lighter stem water oxygen isotope enrichment (δ18O) signature signifying deeper water capture, 13% greater leaf relative water content, 33% greater shoot biomass at anthesis, and 57% greater yield than genotypes with high CN. These results support the hypothesis that low CN improves drought tolerance by increasing rooting depth and water acquisition from the subsoil.